Protective Effects of Carbon Dots Derived from Phellodendri Chinensis Cortex Carbonisata against Deinagkistrodon acutus Venom-Induced Acute Kidney Injury - Zhang, Meiling; Cheng, Jinjun; Sun, Ziwei; Kong, Hui; Zhang, Yue; Wang, Suna; Wang, Xiaoke; Zhao, Yan; Qu, Huihua (Nanoscale research letters, 2019)
Background As an emerging nanomaterial, carbon dots (CDs) have been the focus of tremendous attention for biomedical applications. However, little information is available on their bioactivity of inhibiting acute kidney injury (AKI) induced by snake venom. Methods This study reports the development of a green, one-step pyrolysis process to synthesize CDs using Phellodendri Chinensis Cortex (PCC) as the sole precursor, and their potential application as a protectant against Deinagkistrodon acutus (D. acutus) venom-induced AKI was investigated for the first time. The AKI model was established by injecting D. acutus venom into the abdominal cavity of mice and the potential protective effects of PCC Carbonisata-CDs (PCCC-CDs) on renal abnormalities including dysfunction, inflammatory reactions, tissue damage, and thrombocytopenia at six time points (1, 3, and 12 h, and 1, 2, and 5 days) were investigated. Results These results demonstrated that PCCC-CDs significantly inhibited the kidney dysfunction (reduced serum creatinine (SCR), blood urea nitrogen (BUN), urinary total protein (UTP), and microalbuminuria (MALB) concentrations) and the production of chemoattractant (monocyte chemotactic protein 1 (MCP-1)), proinflammatory cytokines (interleukin (IL)-1β), and anti-inflammatory cytokine (IL-10) in response to intraperitoneal injection of D. acutus venom. The beneficial effect of PCCC-CDs on the envenomed mice was similar to that on the change in renal histology and thrombocytopenia. Conclusions These results demonstrated the remarkable protective effects of PCCC-CDs against AKI induced by D. acutus venom, which would not only broaden the biomedical applications of CDs but also provide a potential target for the development of new therapeutic drugs for AKI induced by D. acutus snakebite envenomation.